Response of Common Bean (Phaseolus vulgaris L.) to Endomycorrhizal Inoculation under Different Phosphorus Application Levels in South-Kivu, Eastern DRC - Ndeko, Byamungu Adrien; Chuma, Géant Basimine; Mondo, Jean Mubalama; Ndusha, Bintu Nabintu; Mushagalusa, Gustave Nachigera (PLANTA TROPIKA, 2023)
Arbuscular mycorrhizal fungi (AMF) have been reported to increase yield and phosphorus (P) uptake. However, it is still unclear how the common bean responds to mycorrhizal inoculation when there is a phosphate supply. This research focused on finding out how bean performance will be affected by mycorrhizal inoculation and increasing P dosages in order to reduce phosphate input. The study was conducted during the A 2021 cropping season in Kabare, while a split-plot design was used to compare two levels of inoculation and increasing phosphorus doses. Rhizophagus irregularis inoculation significantly improved mycorrhizal colonization, biomass, yield, and harvest index of beans at 0 and 30 kg P ha-1. Bean plants inoculated with R. irregularis performed better in terms of biomass, yield, and harvest index at 30 kg P ha-1 than non-inoculated and inoculated plants at 60 and 120 kg P ha-1, indicating the potential of AMF in lowering phosphate input. Phosphorus levels of 60 and 120 kg P ha-1 significantly decreased mycorrhizal infection, indicating the impact of inorganic P on the mycorrhizal symbiosis. In the ferralitic soils of Kashusha, mycorrhizal inoculation with R. irregularis may be a key tool for increasing bean production and ensuring phosphate fertilizer savings.